Exploring Unique Extracellular Vesicles Associated Signatures: Prognostic Insights, Immune Microenvironment Dynamics, and Therapeutic Responses in Pancreatic Adenocarcinoma - Kai Nan; Ming Zhang; Zilong Geng; Yuankai Zhang; Lin Liu; Zhi Yang; Peng Xu (Mediators of Inflammation)
Extracellular vesicles play an important role in the progression of pancreatic adenocarcinoma (PAAD) through the transfer of proteins, mRNAs, and long noncoding RNAs (lncRNAs). However, the intricate interplay between extracellular vesicles-related lncRNAs and the tumor microenvironment (TME) remains poorly elucidated. Consequently, our investigation aimed to delineate the association between extracellular vesicles-related lncRNAs and the PAAD microenvironment. Initially, we identified differentially expressed lncRNAs (DELs) from The Cancer Genome Atlas (TCGA) and Genotype-Tissue Expression (GTEx) project datasets. Subsequently, we validated the expression of these DELs within extracellular vesicles and assessed their prognostic implications in PAAD using the GSE133684 and TCGA datasets. Multiomics data were analyzed comprehensively, including genomic landscape, functional annotation, immune profiles, and therapeutic responses. Differential expression of selected lncRNAs in both cellular and exosomal fractions of PAAD was further confirmed through quantitative polymerase chain reaction (qPCR). Eight DELs were identified from TCGA and GTEx datasets, and two exosomal lncRNAs exhibited a significant correlation with overall survival, warranting further investigation. Specifically, elevated expression of LINC00996 correlated positively with immune infiltration and enhanced response to immunotherapy. Conversely, heightened expression of TRHED-AS1 was associated with compromised immune cell infiltration and diminished responsiveness to immunotherapy. Our study establishes a compelling link between two extracellular vesicles-related gene signatures, prognosis, and immune infiltration in PAAD. Notably, these signatures serve as robust prognostic indicators for PAAD patients, offering valuable insights for the strategic selection of immunotherapeutic interventions.